Effects of different drying methods on the functional properties and physicochemical characteristics of chia mucilage powder (Salvia hispanica L.) - Norashikin Mohd Zain; Maaruf Abd. Ghani; Zalifah Mohd Kasim; Haslaniza Hashim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Chia seeds are a healthy source of omega-3 fatty acids and dietary fibre. The effects of different drying methods (freeze-drying and oven-drying) on the functional properties (water holding capacity, oil holding capacity and colour analysis) and physicochemical characteristics (scanning electron microscopy) of chia mucilage powder (Salvia hispanica L.) including comparison with xanthan gum, hydroxypropyl methylcellulose (HPMC), and arabic gum were investigated. Chia mucilage dried in a freeze dryer (FD) showed significantly higher (p<0.05) values of water holding and oil holding capacities compared to chia mucilage dried in air convection heat oven (ACHO), xanthan gum, HPMC and arabic gum. It also showed a higher L* value (lightness) than ACHO, HPMC, and xanthan gum but lower values of a*, b*, c*, BI, and ΔE than ACHO and xanthan gum. The morphology of FD is smaller, more uniform in size, with a fine fibrous relative structure compared to ACHO. FD is a novel mucilage that could potentially be used as a functional and environmentally friendly hydrocolloid for human consumption and significantly better than commercial hydrocolloids. These results can also help to select successful drying methods for food products based on their functional and physicochemical characteristics.